2002
DOI: 10.2214/ajr.178.5.1781075
|View full text |Cite
|
Sign up to set email alerts
|

Too Few Radiologists?

Abstract: Those in the field of diagnostic radiology should consider measures to mitigate the increasing shortage, while monitoring developments that might signal departures from current trends in supply and demand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…The American College of Radiology currently reports that about 21 000 members are diagnostic radiologists (29). In 2002, Bhargavan et al (30) (34). Exposures to physicians have increased in certain medical specialties in which fluoroscopically guided interventions are performed routinely, however, and these physicians, including interventional radiologists, are the subject of a separate investigation (3).…”
Section: Medical Physics: Long-term Mortality In Radiologists Comparementioning
confidence: 99%
“…The American College of Radiology currently reports that about 21 000 members are diagnostic radiologists (29). In 2002, Bhargavan et al (30) (34). Exposures to physicians have increased in certain medical specialties in which fluoroscopically guided interventions are performed routinely, however, and these physicians, including interventional radiologists, are the subject of a separate investigation (3).…”
Section: Medical Physics: Long-term Mortality In Radiologists Comparementioning
confidence: 99%
“…most, but not all, patients with cancerous growths do not have them in both breasts), then the number of non-cancerous images increases significantly: giving two for each non-cancerous case and one for most cancerous growths. For the volumes studied, of the 75 usable positive cases, 3 of difficulty of the classification problem. The imbalance in the data was mitigated in all cases by using Proportional Individualised Random Sampling, as described in [8] Based on this master dataset, we consider several setups representing different configurations of breasts, segments and views (see Table 1).…”
Section: Dataset Constructionmentioning
confidence: 99%
“…Request permissions from permissions@acm.org. The introduction of breast screening programs has contributed to a significantly higher demand for radiologists, and a world wide shortage of qualified radiologists who specialize in mammography [3] has led to many radiologists being dangerously overworked [2]. This is likely to lead to (i) there being insufficient time for radiologists to interpret mammograms (which are notoriously difficult to read); (ii) an inability to provide redundant readings (second reader); and (iii) radiologists being overly conservative, which in turn is likely to increase the number of patient call backs, potentially resulting in unnecessary biopsies which may lead to patient anxiety and mistrust of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Bhargavan et al [6] reported on their assessment indicating that the current deficit of candidates is 5% and that the shortage could increase to 50% (more than 15,000 radiologists) by 2020.…”
Section: The Fellowship-driven Labor Marketmentioning
confidence: 99%